A proposed student personnel program for Nakhon Sawan Teachers' College, Thailand - Ketkeaw, Bira 1941- (Quezon City [s.n.], 1972)
This paper is an attempt to propose a student personnel program for Nakhon Sawan Teachers' College in Nakhon Sawan, Thailand, based on the student personnel's point of view. Under this educational concept, the attainment of the total development of the student's physical, social, moral, spiritual and intellectual being is considered the fundamental objective of the program.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Nakhon Sawan Teachers' College (Thailand.); Personnel service in education -- Thailand